2007
DOI: 10.1177/0883911507084653
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Doxorubicin from Biodegradable PEG Hydrogels Having Schiff Base Linkages†

Abstract: In our quest to develop new drug delivery systems, we designed and synthesized PEG-conjugates and PEG-hydrogels with a degradable linkage to the drug. Specifically, methoxyPEG-doxorubicin (MPEG-CH=N-Doxo) and doxorubicin-PEG aldehyde (OHC-PEG-CH=N-Doxo) conjugates, plus poly (vinyl amine)-PEG-doxorubicin (PVAm-PEG-Doxo) hydrogels were prepared. The hydrogels were crosslinked by PEG-Schiff base linkages, and the Doxo was conjugated to the gel by pendant Schiff base bonds (PVAm-N=CH-PEG-CH=N-Doxo). The release p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 23 publications
0
65
0
Order By: Relevance
“…[5g] Among dynamic covalent bonds, the benzoic imine bond [6] is especially attractive, because whereas it is stable under physiological conditions, the linker can be hydrolyzed under mildly acidic conditions close to the extracellular pH of solid tumors. [7] Although dynamic covalent bonding has been used widely in the controlled formation of various supramolecular systems, the usefulness as a driving force for fabrication of polymeric superamphiphiles has not been reported.…”
mentioning
confidence: 99%
“…[5g] Among dynamic covalent bonds, the benzoic imine bond [6] is especially attractive, because whereas it is stable under physiological conditions, the linker can be hydrolyzed under mildly acidic conditions close to the extracellular pH of solid tumors. [7] Although dynamic covalent bonding has been used widely in the controlled formation of various supramolecular systems, the usefulness as a driving force for fabrication of polymeric superamphiphiles has not been reported.…”
mentioning
confidence: 99%
“…In order to improve their loading capacity as drug delivery systems, water soluble drugs functionalized with amino groups (e.g., doxorubicin) can be pre-conjugated onto the Dex-CHO chains before the gelation reaction. Similar study on PEG hydrogel-based drug delivery system was reported by Hoffman et al (Saito et al, 2007). In their study, doxorubicin was conjugated to PEG gel by pendant Schiff base linkages, which showed a pH dependant release profile.…”
Section: Figmentioning
confidence: 53%
“…Therefore, hydrogels cross-linked with Schiff bases would show good biocompatibility and biological activity as biomaterials. Moreover, Schiff bases are biodegradable via hydrolysis, and their stability decreases as the surrounding pH decreases, which makes pH-trigged drug release from the Schiff base contained hydrogels possible under physiological conditions (Kratz, Beyer & Schütte, 1999;Saito, Hoffman & Ogawa, 2007).…”
Section: Preparation Of Dextran-based Hydrogelmentioning
confidence: 99%
“…A triggered release can be achieved by the utilization of a specific linker molecule between drug and polymer which is cleavable upon the appliance of a certain trigger. [298][299][300][301] An interesting example to realize this concept was recently described by Choi et al The investigated approach is based on a doxorubicin-PAMAM dendrimer conjugate where the hydrophilic drug is connected to the preformed dendrimer via a photo-cleavable linker. 302 As this was shown to be highly efficient for the release of doxorubicin upon irradiation, it is of great interest to extend this conception to a broad variety of polymeric carrier systems such as e.g.…”
Section: Light-sensitive Microgel-doxorubicin Conjugates: Labile Drugmentioning
confidence: 99%
“…308 The covalent attachment of a drug to a hydrophilic polymeric carrier system via a cleavable molecule and the triggered degradation of the linker is another promising method. [301][302] Investigations on light-sensitive materials based on both of the described concepts are part of this thesis and were described in previous chapters (see chapter 5.3 and 5.4). …”
Section: Towards Stimuli-responsive Core/shell Nanoparticles Containimentioning
confidence: 99%